The price-volume relationship in Malaysia’s commodity futures markets / Siti Zawiah Zainal - Zainal, Siti Zawiah (2007)
This project paper study on the co integrated between return and trading volume in commodity futures market in Malaysia. This study use Crude Palm Oil Futures (FCPO) as a sample of the study. Correlation and Granger causality test are used to investigate contemporaneous and lead-lag relationships between trading volume and both signed and absolute return. Beside that, the study also using the data from FCPO volume and price that taken from Bursa Malaysia from year 1997 until 2006. The topics featured include the significant causality following from trading volume to return or from return to trading volume. The nearby future closing and settlement price are selected in this study. To look the causality of FCPO volume and price Augmented Dickey Fuller and Phillip Peron had been used. The results show a significantly positive causality following trading volume to return in FCPO. From the empirical study found that if the changes in volume cause the price, this may suggest that the speculative activity is relatively high in these commodity futures markets.